2020
DOI: 10.21273/horttech04473-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Type and Source on Pollinator-friendly Plant Purchasing

Abstract: The number of pollinators has been reported to be decreasing for the past several decades. Numerous sources (e.g., climate change, pesticides, loss of habitat) have been noted as potential contributing factors to the decline. With respect to the green industry, the impact of pesticides on pollinator decline and consumer response to this impact is of critical importance. Although no definitive link exists of pesticides being a major contributing factor to pollinator decline, some retailers have banned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Echoing Campbell and Steele (2020), we confirmed that both negative and balanced information treatments significantly increased participants' preferences for labels disclosing the absence of neonicotinoids. In line with the GM food labeling preference literature, the negative information treatment was found to have a more substantial impact than the balanced information treatment likely due to negativity bias effects.…”
Section: Preferences For Labels Disclosing the Absence Or Presence Of Neonicotinoidssupporting
confidence: 62%
See 4 more Smart Citations
“…Echoing Campbell and Steele (2020), we confirmed that both negative and balanced information treatments significantly increased participants' preferences for labels disclosing the absence of neonicotinoids. In line with the GM food labeling preference literature, the negative information treatment was found to have a more substantial impact than the balanced information treatment likely due to negativity bias effects.…”
Section: Preferences For Labels Disclosing the Absence Or Presence Of Neonicotinoidssupporting
confidence: 62%
“…For instance, studies analyzing consumer preferences for pollinator-friendly products (e.g. Campbell and Steele, 2020;Rihn and Khachatryan, 2016;Wei et al, 2020;Wollaeger et al, 2015) are growing in the eco-labeling and production practice related literature (Bougherara and Combris, 2009;Meise et al, 2014;Michaud et al, 2013;Sörqvist et al, 2015;Van Loo et al, 2015). However, none of the previous efforts investigated whether providing issue-specific information (i.e.…”
Section: Background On Neonicotinoid Insecticidesmentioning
confidence: 99%
See 3 more Smart Citations